2022
DOI: 10.3390/children9070940
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Natural Disasters on Maternal Health: Hurricanes Irma and María in Puerto Rico

Abstract: The PROTECT research Center funded by the NIH’s National Institute of Environmental Health Sciences (NIEHS) Superfund Research Program was launched in 2010 to explore the impact of exposure to pollutants on the high rate of premature births in Puerto Rico. In September 2017, Hurricanes Irma and María devastated the archipelago, which caused: collapse of the electrical system, collapse of the communication system, limited access to clean water, food, gas, and health services, destruction of public (e.g., hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…The backgrounds of the articles discuss historical disasters and pandemic occurrences and accordingly the causative lack of disaster preparedness resulting in increased maternal and neonatal deaths during these events. The resources also discuss the increased surge of pregnant and postpartum patients and health complications, seeing that this population is especially vulnerable to disasters [3].…”
Section: Resultsmentioning
confidence: 99%
“…The backgrounds of the articles discuss historical disasters and pandemic occurrences and accordingly the causative lack of disaster preparedness resulting in increased maternal and neonatal deaths during these events. The resources also discuss the increased surge of pregnant and postpartum patients and health complications, seeing that this population is especially vulnerable to disasters [3].…”
Section: Resultsmentioning
confidence: 99%
“…Pregnant women and newborns are vulnerable in times of disaster, and recent large‐scale disasters in various locations worldwide have had a major impact on these patient groups 4–9 . Several studies have reported higher rates of preterm births and low‐birth‐weight infants during large‐scale disasters 10–12 .…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women and newborns are vulnerable in times of disaster, and recent large-scale disasters in various locations worldwide have had a major impact on these patient groups. [4][5][6][7][8][9] Several studies have reported higher rates of preterm births and low-birth-weight infants during large-scale disasters. [10][11][12] In areas affected by the Great East Japan Earthquake, future need of a new acute perinatal care management system was identified, focused on the special needs of affected pregnant and nursing mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The economic recession resulting from the COVID-19 pandemic has adversely affected many people’s mental health and created new barriers for people already suffering from mental illness [ 81 ]. This is not only limited to COVID-19 pandemic, as such negative impacts on mental health and neuropsychiatric conditions have been seen in other global or regional shocks including wars [ 82 , 83 , 84 ], natural disasters [ 85 , 86 ], or other disease outbreaks, e.g., with Ebola [ 87 , 88 ], Zika virus [ 89 ], Middle East respiratory syndrome coronavirus (MERS) [ 90 , 91 ], and severe acute respiratory syndrome coronavirus (SARS-CoV) [ 90 ]. Social isolation due to lockdown or quarantine may have been particularly detrimental to individuals with neuropsychiatric and neurodevelopmental disorders, as social interaction and exercise may be used to regulate several symptoms of these disorders [ 46 , 92 ].…”
Section: Discussionmentioning
confidence: 99%